1990
DOI: 10.1152/ajpheart.1990.259.6.h1643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ANP-(95-126) in dogs before and after induction of heart failure

Abstract: In conscious dogs with and without congestive heart failure, we investigated hemodynamic, hormonal, and renal effects of a new natriuretic peptide [ANP-(95-126)]. Unlike ANP-(99-126), which is secreted in the heart and rapidly inactivated in the kidney, ANP-(95-126) most likely originates from the kidney and is not destroyed by proteolysis in membrane preparations of kidney cortex. In healthy animals intravenous ANP-(95-126) significantly decreased mean arterial pressure, cardiac output, stroke volume, and rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…In normal subjects, bolus injections of URO induced natriuresis and diuresis, which were twice as large as those obtained with similar doses of ANP (Saxenhofer et al, 1990). Similar findings were documented in rats (Abassi et al, 1992b) and dogs (Riegger et al, 1990;Villarreal et al, 1991) with experimental congestive heart failure (CHF).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In normal subjects, bolus injections of URO induced natriuresis and diuresis, which were twice as large as those obtained with similar doses of ANP (Saxenhofer et al, 1990). Similar findings were documented in rats (Abassi et al, 1992b) and dogs (Riegger et al, 1990;Villarreal et al, 1991) with experimental congestive heart failure (CHF).…”
Section: Introductionsupporting
confidence: 59%
“…by others, and was shown to have a very flexible N-terminal segment (Kobayashi et al, 1988 (Cody et al, 1986) or experimental animals (Riegger et al, 1988;Hoffman et al, 1988;Abassi et al, 1990; with congestive heart failure (CHF) is attenuated, and even blunted in severe stages of the disease. In contrast, infusion of equimolar doses of URO into rats with CHF (Abassi et al, 1992b) or dogs with CHF (Riegger et al, 1990;Villarreal et al, 1991), and into healthy individuals and animals (Saxenhofer et al, 1990;Hildebrandt et al, 1992;Bestle & Bie, 1993), increased sodium excretion more than ANP. These differences in the potency of URO and ANP at the renal level may be explained partially by the relative resistance of URO to NEP, so that it reaches its target, namely, the distal segment of the nephron, in greater amounts, and thereby induces greater sodium excretion.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…With respect to this effect the pathophysiological differences between URO and CDD/ANP-99-126 are of interest [34]. Data suggest that URO is a more potent natriuretic agent than CDD/ANP-99-126 in vivo [28,35,36]. The mechanisms underlying this strong natriuretic potency in the kidney have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Abassi et al [56.101] found URO to more effectively induce diure sis and natriuresis at equimolar concentrations ofURO and CDD/ANP-99-126. Rieggeret al [102] observed in experi mentally cardiomyopathic dogs with low-output heart fail ure that URO. but not A-type NP.…”
Section: Pharmacology Of Uromentioning
confidence: 95%